Значення генотипічної мінливості в аспекті адаптаційної здатності рослин - Termena, B.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
Genotypic aspects of plant adaptation was analyzed. Many researches came to conclusion, that modern natural habitats do not represent potential adaptation abilities of plants. It is confirmed by long-term experience of introduction of arboreal plants in Carpathians and Western Podol'e. Supposition, that information is coded in the genotype of plants, which is decrypted in stress situations are shown.